Penentuan Harga Pokok Produksi Kerupuk Berdasarkan Metode Fuzzy Sugeno - Agus Ristono; Pramadhana Alif Hossen (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2025)
Mulya Jaya is a cracker manufacturing SME that faces problems in calculating its cost of goods manufactured (COGM) due to the lack of structured records related to raw material costs, variable overhead costs, and other production costs. This condition makes it difficult for SMEs to determine the right selling price and reduces their competitiveness and profitability. This study aims to determine COGM using the Fuzzy Sugeno method. The data on production costs are converted into fuzzy sets and membership functions, then analyzed using Matlab to obtain COGM estimates. Validation is carried out by comparing the COGM calculation results with actual profits, resulting in an error rate of 7.49%, which indicates that the Fuzzy Sugeno method is highly accurate. In addition, a sensitivity test was conducted to analyze the impact of cost changes on operational stability. The results of the study indicate that Mulya Jaya need to set up mitigation strategies when there is an increase in costs, up to 45% for raw materials and variable overheads, and up to 50% for raw material costs. The strategy that can be applied is to optimize the use of raw materials by adjusting product size and seasoning levels to maintain business sustainability.